Activating Natural Killer Cell Receptors, Selectins, and Inhibitory Siglecs Recognize Ebolavirus Glycoprotein - Mostafa Jarahian (Journal of Innate Immunity, 2021)
Expression of the extensively glycosylated Ebolavirus glycoprotein (EBOV-GP) induces physical alterations of surface molecules and plays a crucial role in viral pathogenicity. Here we investigate the interactions of EBOV-GP with host surface molecules using purified EBOV-GP, EBOV-GP-transfected cell lines, and EBOV-GP-pseudotyped lentiviral particles. Subsequently, we wanted to examine which receptors are involved in this recognition by binding studies to cells transfected with the EBOV-GP as well as to recombinant soluble EBOV-GP. As the viral components can also bind to inhibitory receptors of immune cells (e.g., Siglecs, TIM-1), they can even suppress the activity of immune effector cells. Our data show that natural killer (NK) cell receptors NKp44 and NKp46, selectins (CD62E/P/L), the host factors DC-SIGNR/DC-SIGN, and inhibitory Siglecs function as receptors for EBOV-GP. Our results show also moderate to strong avidity of homing receptors (P-, L-, and E-selectin) and DC-SIGNR/DC-SIGN to purified EBOV-GP, to cells transfected with EBOV-GP, as well as to the envelope of a pseudotyped lentiviral vector carrying the EBOV-GP. The concomitant activation and inhibition of the immune system exemplifies the evolutionary antagonism between the immune system and pathogens. Altogether these interactions with activating and inhibitory receptors result in a reduced NK cell-mediated lysis of EBOV-GP-expressing cells. Modulation of these interactions may provide new strategies for treating infections caused by this virus.